Answer:
y= 2x-1/2 is x=.5 y + .25
2x-3y=4 is x = 1.5y + 2
Step-by-step explanation:
pretty sure thats it
Answer:
f(g(x)) = x^4 + 12x^3 + 14x^2 -132x + 123
Step-by-step explanation:
Here, we simply will place g(x) into f(x)
So every x in f(x) is replaced by g(x)
Thus, we have;
(x^2 + 6x + 11)^2 + 2
= (x^2+6x-11)(x^2 + 6x -11) + 2
= x^4 + 6x^3 -11x^2 + 6x^3 + 36x^2 - 66x -11x^2 -66x + 121 + 2
= x^4 + 12x^3 + 14x^2 -132x + 123
Answer:
1.3 ft
Step-by-step explanation:
perimeter = 140/35 = 4 ft
diameter = 4 ft/ 3.14 = 1.3 ft
If rooster = 6 eggs =10 banana = 5 and 6+10x5= 56